2016
DOI: 10.20886/jphka.2016.13.1.15-28
|View full text |Cite
|
Sign up to set email alerts
|

Komposisi Flora dan Keragaman Tumbuhan di Hutan Rawa Musiman, Rimbo Tujuh Danau Riau

Abstract: Freshwater swamp forest is the most productive ecosystem and plays an important role in the ecological system. The aimed of this study was to analyze structure, composition, plant diversity and to identify the important abiotic environment factors influencing plant diversity on seasonal Tujuh Danau Swamp Forest, Riau. This study was carried out with the quadrat plot methods. In total 200 plots were laid on 1,000 ha area. The result revealed that 97 species of 36 families were identified in the study site. Seed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
2
0
6

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 2 publications
(2 reference statements)
0
2
0
6
Order By: Relevance
“…(Tabel 1). Penelitian Lisdayanti et al, (2016), melaporkan bahwa famili Myrtaceae di hutan rawa air tawar Rimbo Tujuh Danau merupakan salah satu famili yang memiliki anggota spesies lebih banyak dibandingkan famili lainnya.…”
Section: Analisis Dataunclassified
See 3 more Smart Citations
“…(Tabel 1). Penelitian Lisdayanti et al, (2016), melaporkan bahwa famili Myrtaceae di hutan rawa air tawar Rimbo Tujuh Danau merupakan salah satu famili yang memiliki anggota spesies lebih banyak dibandingkan famili lainnya.…”
Section: Analisis Dataunclassified
“…Menurut Setiadi (2005), nilai indeks keanekaragaman dapat berkisar antara 0-7, dengan kriteria: 0-2 (rendah), 2-3 (sedang), dan > 3 (tinggi). Selain itu, menurut Lisdayanti et al (2016), bahwa indeks keragaman menggambarkan tingkat kestabilan dalam suatu komunitas. Secara umum pada lokasi yang diamati bahwa komunitas hutan rawa air tawar di TWA Jering Menduyung dalam kondisi yang kurang stabil.…”
Section: Indeks Keragaman Komunitasunclassified
See 2 more Smart Citations
“…The forest inventory activities have been conducted in natural forest Sumatra by many researchers, but no report that find E. apiculata species (Wardah, 2005;Heriyanto et al, 2006;Rahayu et al, 2007;Setyowati and Wardah, 2007;Kuswanda and Antoko, 2008;Puspitaningtyas and Wawaningrum, 2009;Arifiani and Mahyuni, 2012;Silalahi and Nisyawati, 2015;Ismaini et al, 2015;Lisdayanti et al, 2016;Surya and Astuti, 2017;Des et al, 2017;Susanti et al, 2018;Nasution et al, 2018;Nursanti et al, 2018;Fauzi et al, 2019), except only reported by Nooteboom (1962) and Padua et al, (1999). The question arises, is Eurycoma apiculata in Sumatra (Indonesia) still exist or extinct?…”
Section: Introductionmentioning
confidence: 99%